Jaw and Long Bone Marrows Have a Different Osteoclastogenic Potential - de Souza Faloni, Ana Paula [UNESP]; Schoenmaker, Ton; Azari, Azin; Katchburian, Eduardo; Cerri, Paulo Sérgio [UNESP]; de Vries, Teun J.; Everts, Vincent (Springer, 2011)
Osteoclasts, the multinucleated bone-resorbing cells, arise through fusion of precursors from the myeloid lineage. However, not all osteoclasts are alike; osteoclasts at different bone sites appear to differ in numerous respects. We investigated whether bone marrow cells obtained from jaw and long bone differed in their osteoclastogenic potential. Bone marrow cells from murine mandible and tibiae were isolated and cultured for 4 and 6 days on plastic or 6 and 10 days on dentin. Osteoclastogenesis was assessed by counting the number of TRAP(+) multinucleated cells. Bone marrow cell composition was analyzed by FACS. The expression of osteoclast- and osteoclastogenesis-related genes was studied by qPCR. TRAP activity and resorptive activity of osteoclasts were measured by absorbance and morphometric analyses, respectively. At day 4 more osteoclasts were formed in long bone cultures than in jaw cultures. At day 6 the difference in number was no longer observed. The jaw cultures, however, contained more large osteoclasts on plastic and on dentin. Long bone marrow contained more osteoclast precursors, in particular the myeloid blasts, and qPCR revealed that the RANKL:OPG ratio was higher in long bone cultures. TRAP expression was higher for the long bone cultures on dentin. Although jaw osteoclasts were larger than long bone osteoclasts, no differences were found between their resorptive activities. In conclusion, bone marrow cells from different skeletal locations (jaw and long bone) have different dynamics of osteoclastogenesis. We propose that this is primarily due to differences in the cellular composition of the bone site-specific marrow.
Keywords: Jaw; Long bone; Osteoclastogenesis; Osteoclast precursor; Heterogeneity; Marrow